2020
DOI: 10.2217/pmt-2019-0045
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Methylnaltrexone for Opioid-Induced Constipation in Advanced-Illness Patients With or Without Active Cancer

Abstract: Aim: To evaluate methylnaltrexone for opioid-induced constipation in patients with and without cancer. Methods: This post hoc analysis comprises two Phase III, multicenter, double-blind, randomized studies of advanced-illness patients who received methylnaltrexone subcutaneous injection or placebo. Results: Significantly more patients treated with methylnaltrexone than placebo experienced laxation within 4 (cancer = 55.5 vs 15.5%; noncancer = 55.6 vs 12.8%) and 24 (cancer = 64.7 vs 29.8%; noncancer = 64.4 vs 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Several randomised, double-blind, placebocontrolled trials have investigated the efficacy and safety of methylnaltrexone both in patients with cancer-related [140][141][142][143] and non-cancerrelated [144][145][146][147] pain. In addition, meta-analyses have shown that methylnaltrexone improves bowel function (both subjectively and objectively), is well tolerated and reduces healthcare resource utilisation, but does not compromise the analgesic efficacy of concomitantly administered opioids [148,149].…”
Section: Second-line Treatmentmentioning
confidence: 99%
“…Several randomised, double-blind, placebocontrolled trials have investigated the efficacy and safety of methylnaltrexone both in patients with cancer-related [140][141][142][143] and non-cancerrelated [144][145][146][147] pain. In addition, meta-analyses have shown that methylnaltrexone improves bowel function (both subjectively and objectively), is well tolerated and reduces healthcare resource utilisation, but does not compromise the analgesic efficacy of concomitantly administered opioids [148,149].…”
Section: Second-line Treatmentmentioning
confidence: 99%
“…15 Common treatments for constipation include dietary and lifestyle interventions (such as increased fibre and/or exercise) and/or laxatives (including stimulants, stool softeners, and fibre supplements). 16 Although there is some information and evidence to inform the treatment of opioid-induced constipation in patients receiving prescribed opioids, [17][18][19] less information is known to be available to inform best practices for treating OUD patients with constipation as a side effect of OAT or MMT.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…22 Most of the evidence in this topic area was found to address either the clinical effectiveness of OAT and/or MMT 28,29 or the side effects from prescribed opioid medications in patients living with pain. [17][18][19]30,31 Although existing guidelines offer recommendations about the use of OAT and/or MMT to treat OUD, there were no guidelines identified informing the management or treatment of constipation or ED as side effects of OAT and/or MMT. 1,8 CADTH has previously assembled a body of evidence relevant to opioids, 32,33 including reports that have assessed and summarized evidence specific to the use of OAT and MMT and its effects on people living with OUD.…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 99%
See 2 more Smart Citations